1997
DOI: 10.1091/mbc.8.11.2307
|View full text |Cite
|
Sign up to set email alerts
|

A Novel RING Finger Protein Complex Essential for a Late Step in Protein Transport to the Yeast Vacuole

Abstract: Protein transport to the lysosome-like vacuole in yeast is mediated by multiple pathways, including the biosynthetic routes for vacuolar hydrolases, the endocytic pathway, and autophagy. Among the more than 40 genes required for vacuolar protein sorting (VPS) inSaccharomyces cerevisiae, mutations in the four class CVPS genes result in the most severe vacuolar protein sorting and morphology defects. Herein, we provide complementary genetic and biochemical evidence that the class C VPSgene products (Vps18p, Vps1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
284
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 296 publications
(301 citation statements)
references
References 94 publications
(127 reference statements)
14
284
0
Order By: Relevance
“…Class C Vps/HOPS proteins consist of a tethering protein complex including an SM (Sec1/Munc18-like) protein and a Rab GEF (GDP/GTP exchanger) for Ypt7, and are involved in fusion. 36,46 Recently, it was found that the mammalian HOPS complex binds to UVRAG, which is a Beclin-1 binding protein. 47 Beclin-1, the mammalian homologue of yeast Atg6, also interacts with class III phosphatidylinositol 3-kinase/ hVps34 and is essential for autophagosome formation.…”
Section: Transport and Fusionmentioning
confidence: 99%
“…Class C Vps/HOPS proteins consist of a tethering protein complex including an SM (Sec1/Munc18-like) protein and a Rab GEF (GDP/GTP exchanger) for Ypt7, and are involved in fusion. 36,46 Recently, it was found that the mammalian HOPS complex binds to UVRAG, which is a Beclin-1 binding protein. 47 Beclin-1, the mammalian homologue of yeast Atg6, also interacts with class III phosphatidylinositol 3-kinase/ hVps34 and is essential for autophagosome formation.…”
Section: Transport and Fusionmentioning
confidence: 99%
“…However, the promiscuity of SNARE-SNARE interactions may allow other post-Golgi t-SNAREs to substitute at least in part for the loss of the relevant late Golgi t-SNARE. In fact, loss of the vacuolar t-SNAREs Vam3p and Vam7p results in less severe defects in vacuolar morphology and function than loss of the class C proteins Vps11p, Vps18p, Vps16p, and Vps33p, which act together to regulate the fusion of multiple transport intermediates with the vacuole, and high levels of the prevacuolar t-SNARE Pep12p suppress mutations in VAM3 (Darsow et al, 1997;Rieder and Emr, 1997). It is also difficult to extrapolate from the phenotypes resulting from defects in t-SNAREs, because these proteins are likely to regulate a number of different transport events.…”
Section: Function Of the Vps52/53/54 Complex In Golgi Sortingmentioning
confidence: 99%
“…These include Vac1p, the yeast homologue of EEA1, which binds the Rab5 homologue Vps21p as well as the Sec1-like Vps45p and the endosomal t-SNARE Pep12p (Burd et al, 1997;Peterson et al, 1999;Tall et al, 1999). Class C Vps proteins include Vps11p, Vps18p, Vps16p, and the Sec1-like Vps33p, which form a complex that, together with the vacuolar t-SNARE Vam3p, the SNAP-25-like Vam7p, and the Rab protein Ypt7p, is required for the fusion of multiple transport intermediates with the vacuole (Haas et al, 1995;Darsow et al, 1997;Rieder and Emr, 1997;Sato et al, 1998;Ungermann and Wickner, 1998). Class E VPS gene products regulate transit through the PVC, whereas components of the retromer complex are thought to act at the PVC to sort proteins into retrograde vesicles that are targeted to fuse with the TGN (Seaman et al, 1998;Nothwehr et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Deletion of vps genes necessary for fusion of transport vesicles with the PVC or required for fusion of membranes derived from the PVC and from the ALP pathway with the vacuole results in a growth defect at 37°C (Piper et al, 1994;Becherer et al, 1996;Rieder and Emr, 1997). vti1-1 cells do not have a growth defect at the nonpermissive temperature.…”
Section: Vti1p Interacts With Vam3p In Alp Transport To the Vacuolementioning
confidence: 99%
“…The adaptor complex AP3 is required for ALP but not for CPY transport to the vacuole Stepp et al, 1997). Several proteins have been identified as being involved in both ALP and CPY transport to the vacuole, for example, Vam3p, Vam7p and a vacuolar protein complex consisting of Vps18p, Vps11p, Vps16p, and Vps33p (Darsow et al, 1997;Piper et al, 1997;Wada et al, 1997;Rieder and Emr, 1997;Sato et al, 1998;Srivastava and Jones, 1998).…”
Section: Introductionmentioning
confidence: 99%